The Late Cenozoic history and palaeoenvironments of the coastal margin of the south-western Cape Province, South Africa - Tankard, Anthony James Tempest (Rhodes University, Faculty of Science, Department of Geology, 1976)
This thesis examines the Late Cenozoic history and palaeoenvironments of the coastal margin between Elands Bay on the west coast and Die Kelders on the south coast. This study is introduced with a detailed discussion of eustatic sea level oscillation. The history of the existing ice sheets, sea floor spreading, isotopic composition changes of the oceans, and isostatic responses of the crust to varying loads are reviewed with regard to their bearing on sea level changes. A detailed account of the Neogene stratigraphy of the south-western Cape Province is presented. The Middle to early Late Miocene Saldanha Formation is characterised by shallow marine phosphatic sandstone and phosphorite. It is thought to have been deposited in a warm transgressive sea. The Pliocene Varswater Formation was deposited during a secondary transgression induced by.seaward tilting of the coastal margin during a time of worldwide regression. The Varswater Formation is characterised by pelletal phosphorites. It includes marine, estuarine, and fluvial facies. The estuarine sands and peats contain a rich fossil mammal fauna. Depositional environments of the Pelletal Phosphorite Member are examined by means of conventional grain size analysis to show that deposition took place on a shallow sublittoral platform dominated on the outer edge by a breaker-bar. Accretion of the breaker-bar to form a barrier-island allowed the development of an estuarine complex on the leeward side. Post-depositional diagenetic changes were examined by means of scanning electron microscopy. A detailed account of the petrology and geochemistry of the phosphorite and pelletal phosphorite is presented. The apatite mineral is a carbonate fluorapatite. It is concluded that the phosphorite is related to upwelling of phosphorus-rich waters.
Keywords: Uncatalogued